Association of Angiotensin-Converting Enzyme and Angiotensinogen Gene Polymorphisms with Preeclampsia - Choi, Hyunah (The Korean Academy of Medical Sciences, 2004)
We tested the hypothesis that angiotensin-converting enzyme (ACE) and angiotensinogen gene polymorphism influence the incidence, development and outcome of preeclampsia. Subjects were recruited from 90 Korean patients with preeclampsia during pregnancy and 98 age-matched controls. After isolation of DNA, polymerase chain reactions (PCR) were carried out to detect polymorphism of the ACE and angiotensinogen. M235T and T174M genotypes of angiotensinogen were determined by digestion with restriction enzyme endonuclease Tth 111-I and NCo I, respectively. The frequency of DD genotype was significantly greater in preeclampsia (0.36) than in controls (0.14) (p<0.05). The frequency of D allele was 0.55 in preeclampsia and 0.40 in controls (p<0.05). There were no differences in the onset of preeclampsia and pregnancy outcomes according to the ACE genotypes. There was no difference in the frequency of a allele of angiotensinogen M235T between the groups (0.79:0.78 in preeclampsia : controls). The frequency of T allele of angiotensinogen T174M gene was slightly increased, but not significantly, in preeclampsia (0.11) than in controls (0.07). In a multivariate analysis, only ACE genotype was associated with the development of preeclampsia (β=0.27, p=0.05). In conclusion, a molecular variant of ACE, but not angiotensinogen, gene is associated with preeclampsia in Korean women.